Electromyographical Analysis of Table Tennis Forehand Stroke Using Different Ball Material - Maheshwari, Anubha; Pandey, Gayatri; Shukla, Manish; Rawat, Vijay Singh; Yadav, Tanushree (Physical Education Theory and Methodology, 2022)
Research purpose. This study aimed to determine the EMG analysis of forehand topspin using different ball materials. Materials and methods. For the purposes of this study, seven male university-level table tennis players who were right-hand dominant players (age 21.1 ± 2.4 years, height 162.6 ± 6.8 cm, mass 61.8 ± 3.2 kg) with at least 6 years of playing experience were selected. The selected participants were physically active and had no physical injuries. The study was approved by the research committee. Pectoralis Major (PM), Deltoid Anterior (DA), Latissimus Dorsi (LD), Biceps Brachii (BB), Extensor Carpi Radialis (ECR), Flexor Carpi Radialis (FCR) muscles were selected for the electromyographical study. One of the EMG signals variable Root Mean Square was measured in all muscles, through which the maximum muscle involvement was evaluated. For each assessed muscle and both ball materials, the mean value of Root Mean Square EMG signals was computed. For descriptive statistics, minimum, maximum, mean, and standard deviation were used, and a t-test was used as a statistical technique. Results. The level of significance was set at 0.05. Results of the study showed no significant difference in EMG variable Root Mean Square between celluloid and poly plastic ball material on selected muscles. Conclusions. We conclude that the biceps brachii and extensor carpi radialis are important muscles for the forehand topspin because they are responsible for flexion of the arm and work strongly in the action of gripping in the performance of quick forehand spin strokes.